An inventory and routing model using deterministic and stochastic demand. - Belfiore, Patrícia Prado; Costa, Oswaldo Luiz do Valle; Fávero, Luiz Paulo Lopes (Revista Gestão da Produção Operações e Sistemas, 2007)
This paper analyses the inventory routing problem, which is an extension of the traditional vehicle routingproblem. The objective is to develop a problem modeling and to create a methodology of solution based on ahierarchical decision model. The problem consists in determining when and how much merchandise needs to bedelivered to each customer and which delivery routes can be used; the target is to minimize the inventory anddistribution costs, so that the customer´s demands can be attended.Keywords: Inventory; Routing; Deterministic demand; Stochastic demand.